Analysis of fuel gases. Methods for non-manufactured gases. Hydrocarbons and inert gases. Determination of hydrocarbons from butane (C4 ) to hexadecane (C16 ) by gas chromatography Part 11.1.2, (27th February 1987) - British Standards Institution,
No abstract available